DS8000 4-Site Replication with IBM Copy Services Manager - Luther, Thomas; Klee, Peter; Warmuth, Alexander (IBM Redbooks, 2020)
This IBM® Redpaper publication helps you design and implement a 4-site replication solution for IBM DS8000® environments. IBM Copy Services Manager is used to orchestrate the data replication and failover and failback mechanisms between the different sites. The IBM DS8000 Copy Services functions are the foundation of this 4-site replication solution. The four sites consist of two pairs of sites. Within each pair, the two sites are at metro distance, while the pairs connect at long distance over asynchronous links. The solution is based on a Multi-Target PPRC topology that consists of a Metro Mirror replication to the secondary site in the local region and a Global Mirror replication to the third site in the remote region. The fourth site is set up as a cascaded Global Copy, which is an asynchronous copy.
Online resource; Title from title page (viewed February 11, 2020)
Keywords: Computer architecture; Storage area networks (Computer networks); Ordinateurs; Architecture; Réseaux de stockage (Informatique)